PENERAPAN PRINSIP BIOPHILIC DESIGN PADA PERANCANGAN APARTEMEN SOHO DI KOTA PEKANBARU - Kaffah, Mahya Fiddini; Firzal, Yohannes; Susilawaty, Mira Dharma (Unika Santo Thomas, 2020)
The mobile lifestyle among entrepreneurs in Pekanbaru City presents the need for a place to stay that can be used as an office for work. To meet these needs, the concept of SOHO (Small Office Home Office) can be applied to the apartment. Architecture as a space for human activity is also instrumental in increasing human productivity, so it needs to be considered aspects of the physical environment of a workspace, both in terms of layout and comfort. The biophilic design is applied in the design object because it is able to provide comfort to human physique, improve health, fitness, and well-being of human. Therefore, design of SOHO apartment with the application of biophilic design to create an apartment that not only fulfill the need for residence and place of work but also able to align the interests of humans and nature